The Debates of the Createdness of the Qur’an and its Impact to the Methodology of Qur’anic Interpretation - Safrudin Ediwibowo (Ulumuna, 2015)
The status of the Qur'an as the verbatim words of God has become undisputed belief among Muslims. However, beyond the agreement on this fundamental doctrine, they differed from interpreting the nature of "the Qur’an" whether it is eternal and co-existent with God or created by God like other beings in this world? Throughout Islamic history, there are at least two major trends in interpreting the nature of the Qur’an as God words, i.e. scholars who believe in the eternity of the Qur’an and those who believe in the createdness of the Qur’an. A number of Muslim thinkers since three decades ago have adopted the concept of the createdness of the Qur’an to support their methodological principles developed in interpreting the Qur’an. This paper will explore further the origin of the doctrine of eternity and the createdness of the Qur’an, the debate on this issue in classical and contemporary Islamic thoughts and its methodological implications on the interpretation of the Holy Scripture. DOI: http://dx.doi.org/10.20414/ujis.v19i2.357